PSYCHOCHEMICAL AND SENSORY CHARACTERISTIC OF JELAWAT FISH MEAT (Leptobarbus hoevenii) FROM DIFFERENT SIZES - Adi Putra Silaban; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to evaluation and compared chemical proximate composition, amino acid and fatty acid, jelawat fish from different sizes small (400-500 gr), medium (700-800 g), and large (1000-1100 g). Jelawat fish used is 27 from cage in Kampung Jelawat, Kampar. Value of jelawat fish was evaluation, value of edible portion, processing waste, water holding capacity, sensory quality, proximate, amino acid and fatty acid. The research was showed that appearance, odor, edible portion, processing waste was not different between fish size. The highest flavors, texture is found in large sizes fish. The highest water holding capacity is found in medium size fish then large size fish and small size fish. Water content and ash content from large size fish was highest, then followed in a row by medium size fish and large size fish. The protein content of medium size fish is higher than small size fish and large size fish. The highest amino acid is found in large size fish followed by small size fish and medium size fish. The highest fatty acid is found in small size fish followed by medium size fish and large size fish.Kata kunci : Leptobarbus hoevenii, psychochemical and sensory, from different sizes.